Pengembangan Media Pembelajaran RUMPI (Rumah Pintar) Berbasis Android Kelas IV Sekolah Dasar - Shinta Rohadatul 'Aisy; Meifita Asri Untari; Ikha Listyarini (STKIP Andi Matappa Pangkep, 2022)
This research focuses on developing an innovative and interactive android-based learning media to increase learning motivation and make learning more interest. The purpose of this study is to describe the characteristics of the Android-based RUMPI (Smart House) learning media and to determine the level of validity and practicality of the Android-based RUMPI (Smart House) learning media in the IV grade of elementary school. This type of research used Research and Development (RnD) using the ADDIE development model (Analysis, Design, Development, Implementation, and Evaluation). This research is conducted in three elementary schools: SDN Bangunharjo, SDN Miroto, and SDN Pandean Lamper 05. The data in this study was obtained by observation through observation, interviews, and questionnaires. The validation results from the two material experts showed an average percentage of 100% and the validation results from the two media experts showed an average percentage of 100%. The results of the practitioner's assessment obtained a percentage of 96%. Student response questionnaires obtained a percentage of 99%. It can be concluded that the learning media developed are included in the categories of